2000
DOI: 10.1128/mcb.20.1.61-69.2000
|View full text |Cite
|
Sign up to set email alerts
|

Histone H1 Is Dispensable for Methylation-Associated Gene Silencing in Ascobolus immersusand Essential for Long Life Span

Abstract: A gene encoding a protein that shows sequence similarity with the histone H1 family only was cloned in Ascobolus immersus. The deduced peptide sequence presents the characteristic three-domain structure of metazoan linker histones, with a central globular region, an N-terminal tail, and a long positively charged C-terminal tail. By constructing an artificial duplication of this gene, named H1, it was possible to methylate and silence it by the MIP (methylation induced premeiotically) process. This resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 64 publications
3
69
3
2
Order By: Relevance
“…However, there have been an increasing number of examples in which H1 plays a more specific role in transcription by differentially acting at the level of individual genes. The original model for this H1 specificity is based on the results obtained from gene knock-out experiments in Tetrahymena, fungus, and yeast (15,52,53). These studies showed that deletion of H1 gene keeps the organism alive, but specific subsets of genes are differentially regulated.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been an increasing number of examples in which H1 plays a more specific role in transcription by differentially acting at the level of individual genes. The original model for this H1 specificity is based on the results obtained from gene knock-out experiments in Tetrahymena, fungus, and yeast (15,52,53). These studies showed that deletion of H1 gene keeps the organism alive, but specific subsets of genes are differentially regulated.…”
Section: Discussionmentioning
confidence: 99%
“…These observations demonstrate that a nucleosomal architecture containing methylated DNA (22,23,77). In Ascobolus immersus elimination for some transcription factors, acetylation of the amino-terminal tails substantially weakens the conof histone H1 is without effect on methylation-dependent gene silencing (8). Moreover, recent in vivo straints on DNA imposed by the core histones.…”
Section: El-osta and Wolffementioning
confidence: 99%
“…One proposal is that H1 hyperphosphorylation itself might serve as a mitotic "trigger" and not the actual physical means for condensation (Roth and Allis, 1992 These data point towards the fact that specific H1 subtypes and their phosphorylation states may have specific functional roles in chromatin remodeling events which are responsible for transcriptional regulation that takes place during various biological processes such as development, differentiation, DNA repair (Downs et al, 2003), apoptosis (Konishi et al, 2003;Okamura et al, 2007) and lifespan (Barra et al, 2000).…”
Section: Introductionmentioning
confidence: 99%